Identificação e análise de clones de códigos heterogêneos em um ambiente corporativo de desenvolvimento de software - Torres, José Jorge Barreto (2016)
The demand for speeding up software development inside corporations triggers a series of issues related to coding organization. Software development teams have to achieve business deadlines, so they adopt the bad practice to copy-and-paste code. In this way, clones populate software repositories and hinder the improvement or maintenance of systems. Programming languages with object-oriented paradigm characteristics tend to make easy coding abstraction and reuse processes. However, a question arises: the same team working with several kinds of programming languages are influenced by their paradigms regarding the decrease of cloning incidence? This work proposed an approach to identify, analyze and compare clones inside heterogeneous software repositories without consider the development team profile. The experimental evaluation of the approach was possible thru two controlled experiments which aimed to detect and evaluate clones, using and adapting tools available on market. This evaluation was executed inside an organizational environment, which owned several applications with closed-source code but available to analysis. The final results showed no relationship to the amount of application code lines. Procedural language systems had a lower clone incidence and, when conflicting open and closed source systems, both had similar results regarding to the manifestation of source-code clones.